Efektifitas Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Terhadap Pemahaman Nilai-Nilai Moderasi Beragama Siswa - Hayati, Irpini; Nurlaili, Nurlaili (UIN Fatmawati Sukarno Bengkulu, 2024)
The research objectives are to determine the learning of Islamic Religious Education and Character at State High School 10 in Bengkulu City. to determine the understanding of the values of religious moderation of students at State Senior High School 10, Bengkulu City. to determine the effectiveness of learning Islamic Religious Education and Character towards students' understanding of the values of religious moderation at State High School 10 in Bengkulu City. The type of research used is correlational research, which aims to determine the level of relationship between two variables, without making any changes to the data that has been obtained. The population in the research was 753 students from State High School 10, Bengkulu City. Then the sampling technique used was purposive sampling so that a sample of 75 people was obtained. The data collection techniques used are observation, questionnaires and documentation. Based on the research results, it is known that Islamic Religious Education learning in schools is in the medium category, where as many as 44 (58.67%) teachers teach about noble morals, devotion to Allah SWT, teachers train and develop students' cognitive abilities, attitudes and psychomotor skills, and get students used to praying before activities, doing assignments given by the teacher. Students' understanding of religious moderation is in the medium category, where as many as 46 (61.33%) of the students are able to appreciate and respect parents/others, avoid conflict, be fair, not impose their own will, maintain unity, learn and preserve customs, and so on. There is the effectiveness of learning Islamic Religious Education and Character towards students' understanding of the values of religious moderation. Where rcount > rtable, namely rcount: 0.910 while rtable: 0.235, therefore the hypothesis is accepted. This concludes that the school plays a role in understanding students' values of religious moderation.